Executive functions, creativity, and academic performance in Argentine university students. A mediation analysis - Yado, Luz Milagros (2025)
The relationship between executive functions (EF), creative personality, and academic performance in Argentine university students was examined. A total of 248 students (M = 22.97 years, SD = 4.43) from various Argentine provinces participated. The Adult Executive Functioning Inventory (ADEXI), the Cognitive Flexibility Scale, the Creative Behavior Scale (ECC), and the Creative Personality Scale (EPC) were used, along with academic performance data and sociodemographic information. Data were collected online through Google Forms and analyzed using Spearman correlations and mediation analysis with robust Maximum Likelihood estimator and Bootstrap. Cognitive flexibility exhibited the most robust correlation with grade point average (r = .281, p < .001), followed by working memory difficulties (r = -.234, p < .001). Creative personality correlated positively with grade point average (r = .249, p < .001). The mediation analysis confirmed a significant direct effect of cognitive flexibility on academic performance (β = 0.292, p < .001), as well as a weak but significant indirect effect through creative personality (β = 0.088, p = .016), evidencing partial mediation. The model explained 10% of the variance in academic performance. Findings underscore the relevance of cognitive flexibility as the primary predictor of university academic success and a complementary but minor role of creative personality.